A Minimally Invasive Surgical Procedure to Harvest Palate Periosteum as a Source of Mesenchymal Stromal/Stem Cells for Bone Tissue Engineering - André Antonio Pelegrine; David Gonzalo Montero López; Antonio Carlos Aloise; João Pedro Grandini Zeferino; Carolina Guassi Mannina; Raul Canal; Daniel Navarro da Rocha; Tamara Cristina Lopes de Castro; Elizabeth Ferreira Martinez; Lexie Shannon Holliday; Roberto Dalto Fanganiello; José Ricardo Muniz Ferreira (MDPI AG, 2024)
The aim of this study is to validate a minimally invasive surgical procedure to harvest palate periosteum as a source of tissue for mesenchymal stromal/stem cells. We performed a standardized procedure to harvest the palate periosteum in ten subjects, which consisted of a 3 mm disposable punch and a Molt periosteal elevator to harvest a small full-thickness fragment of soft tissue at the hard palate area, between the upper bicuspids, 3 to 4 mm apical to the cement enamel junction. The one-third inner portion was fragmented, and following standard cell culture procedures, the adherent cells were cultured for three passages, after obtaining 70-90% confluence. Cell morphology analysis, flow cytometry analysis, and viability and osteogenic differentiation assays were performed. In all 10 cases, uneventful healing was observed, with no need for analgesic intake. The evaluation of cell morphology showed elongated spindle-shaped cells distributed in woven patterns. A high viability range was verified as well as an immunophenotype compatible with mesenchymal stem cell lineage. The differentiation assay showed the potential of the cells to differentiate into the osteogenic lineage. These results demonstrate that the minimally invasive proposed surgical technique is capable of supplying enough periosteum source tissue for stem cell culture and bone tissue engineering.